Individual Representation : A Different Approach to Political Representation - Ruedin, Didier (My University, 2012)
This article presents a new conceptualisation and measure of political representation to complement conventional approaches. Individual representation scores place the individual rather than the legislature at the centre, providing a fresh perspective on the relationship between inequality and representation. They are calculated by comparing first the position of the individual with other citizens, and second the position of the individual with the legislature. The article outlines how to make sense of individual representation scores and includes an empirical example.
Keywords: Dialogism; Dialogicality; Symbolic resources; Diary